KADAR TOTAL SENYAWA FENOLAT PADA MADU RANDU DAN MADU KELENGKENG SERTA UJI AKTIVITAS ANTIRADIKAL BEBAS DENGAN METODE DPPH (Difenilpikril Hidrazil) - Ratnayani, Ketut; Mayun Laksmiwati, A. A. I. A; Indah Septian P., Ni P. (Jurnal Kimia (Journal of Chemistry), 2013)
Honey contains a variety of compounds which function as antioxidants one of which is a phenolic compound. Monoflora honey used in this study were randu and kelengkeng honey from certain brand distributed on the market. Qualitative test with 5% FeCl 3 result showed that both types of honey contain phenolic compounds. The total phenolic compounds was determined by spectrophotometry using the Folin-Ciocalteu method and gallic acid as standards, while the free radical activity was tested using the method of  DPPH ( Difenilpikril hidrazil ). The result of research showed that the total content of phenolic compound in randu was 1375,89 ± 134,10 mg GAE/kg, while kelengkeng honey was 1136,49 ± 39,62 mg GAE/kg. The % reduction of free radical in randu honey at the 5 th minute was 62,55 ± 4,4407 % and at the 60 th minute was 95,39 ± 8,5507 %. The % reduction of free radical for kelengkeng honey at the 5 th minute was 44,12 ± 1,3433 %, 60 th minute was 62,00 ± 0,8612 %, and for the standard of gallic acid the % reduction of free radical at the 5 th minute was 41,03% and the 60 th minute was 92,00%. Therefore, there was a linear correlation between the total phenolic compound of randu honey and kelengkeng honey with % reduction of its free radical.
Keywords: Honey, phenolic, spectrophotometry UV-Vis, free radical activity